Ark angel - Horowitz, Anthony, 1955- (London : Walker Books, 2005)
After recovering from a near fatal gunshot wound, teenage spy Alex Rider embarks on a new mission to stop a group of eco-terrorists from sabotaging the launch of the first outer space hotel.
Keywords: Spies -- Fiction; Adventure and adventurers -- Fiction; Orphans -- Fiction; Terrorism -- Fiction